Diffusion of innovation in service firms: Hungarian versus Slovakian business service firms - Csaba Makó; Péter Csizmadia; Miklós Illéssy; Ichiro Iwasaki; Miklós Szanyi (Journal for East European Management Studies, 2013)
The current global financial and economic crisis has brought into prominence the patterns of economic modernisation of post-socialist countries in the Central and Eastern European (CEE) region. One of the key factors of successful modernisation and sustainability of competitiveness in these economies is the firms' innovative capability. The paper aims to map and assess the various forms of organisational innovations and their drivers based on original company survey data collected in Hungary and Slovakia among firms operating in the Knowledge Intensive Business Services sector in 2008 and 2009. – – Die aktuelle globale Finanz- und Wirtschaftskrise hat die Muster der wirtschaftlichen Modernisierung der post-sozialistischen Ländern in Mittel- und Osteuropa (CEE) in den Vordergrund gerückt. Einer der wichtigsten Faktoren für erfolgreiche Modernisierung und Nachhaltigkeit der Wettbewerbsfähigkeit in diesen Ländern ist die Innovationsfähigkeit der Unternehmen. Der Artikel zielt darauf ab, die verschiedenen Formern organisationaler Innovationen und ihre Treiber abzubilden und zu bewerten auf der Grundlage einer Befragung von Unternehmen aus dem Bereich der wissensintensiven Unternehmensdienstleistungen in der Slowakei und Ungarn in 2008 und 2009.
Keywords: 650; modernisation; knowledge intensive business services (KIBS); nontechnological innovation; radical and incremental organisational innovation; Innovationsmanagement; Innovationsdiffusion; Innovationswettbewerb; Wissensintensives Unternehmen; Unternehmensdienstleistung; Vergleich; Slowakei; Ungarn